2014
DOI: 10.1371/journal.pone.0097571
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Peripheral Blood Mononuclear Cells of Patients with Common Variable Immunodeficiency: Modulation of Adaptive Immune Response following Intravenous Immunoglobulin Therapy

Abstract: BackgroundRegular intravenous immunoglobulin treatment is used to replace antibody deficiency in primary immunodeficiency diseases; however the therapeutic effect seems to be related not only to antibody replacement but also to an active role in the modulation of the immune response. Common variable immunodeficiency is the most frequent primary immunodeficiency seen in clinical practice.MethodsWe have studied the effect of intravenous immunoglobulin replacement in patients with common variable immunodeficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…3C). The loss of overall CD4 + T cells in CVID patients is well documented (13,(35)(36)(37), and we found that CD4 + T cells were reduced also in this cohort (data not shown). This suggests that the subset of CD4 + T cells expressing CD161 is specifically preserved in CVID patients.…”
Section: Cd4supporting
confidence: 68%
See 1 more Smart Citation
“…3C). The loss of overall CD4 + T cells in CVID patients is well documented (13,(35)(36)(37), and we found that CD4 + T cells were reduced also in this cohort (data not shown). This suggests that the subset of CD4 + T cells expressing CD161 is specifically preserved in CVID patients.…”
Section: Cd4supporting
confidence: 68%
“…It is unknown why CD161 + CD4 + T cells were preserved in CVID, unlike the general loss of CD4 + T cells, which has been well documented (13,(35)(36)(37). This would suggest that CD161 expression identifies a subset of CD4 + T cells that is preserved in CVID.…”
Section: Cd8mentioning
confidence: 99%
“…The significantly different expression of genes observed in microarray assay was validated by testing some selected genes with real‐time polymerase chain reaction (RT‐PCR) in patients and healthy controls. The method adopted for this validation procedure is detailed in the Supplementary section .…”
Section: Methodsmentioning
confidence: 99%
“…However, Artac et al [96] reported that expression of CD69 and HLA-DR by CD8 + T cells is not affected by IVIG. The immunological mechanisms by which IVIG can normalize T-cell counts and function in CVID patients remains unclear, but Dolcino et al [97] reported that lower expression of LEPR, a major gene in CD4 + T-cell proliferation, returned to normal values after IVIG treatment [97]. Artac et al also showed that IVIG causes an increase in the expression of CD95 and CD25 in CVID patients and suggested that CD95 may play a critical role in the effects of IVIG for control of autoimmunity and inflammation in CVID patients.…”
Section: Effects Of Ivig On T Cells In Cvid Patientsmentioning
confidence: 99%